Stomach cancer and occupation in Sweden: 1971–89. Issue 5 (1st May 2002) - Aragonés, N; Pollán, M; Gustavsson, P
Abstract : Objectives: To examine the relation between gastric cancer and occupation among men and women gainfully employed in 1970 in Sweden for the period 1971–89 and, more specifically, to evaluate whether any excess of incidence of gastric cancer had also occurred among the subcohort of people reporting the same occupation in 1960 and 1970. Methods: In both sexes and cohorts, relative risks adjusted for age, period of diagnosis, and geographical risk area were computed for occupational codes specified at one, two, or three level (occupational sector, occupational group, and occupation, respectively). Relative risks were calculated with all other occupations as reference and then, to take socioeconomic status into account, solely other occupations within the same occupational sector were used. Results: Among men, occupations with increased risk included miners and quarrymen, construction and metal processing workers, supporting the possible causative role of dusty environments in stomach cancer. In men, the results also provide support for increased risks among electrical and mechanical engineers, fishermen, petrol station workers, motor vehicle drivers, butchers and meat preparers, dockers, freight handlers, launderers and dry cleaners. Furthermore, it is worth noting interesting results for women, whose occupational risks have been studied less. Excess risks were found for practical nurses, cashiers, bank employees, engineering and electronic industry workers, food industry, housekeeping and cleaning workers. Due to the many occupations studied, several significant associations may be expected by chance. Conclusions: The study is explorative but provides support for the relations suggested previously between occupational exposure to dusty environments and stomach cancer, together with some new high risk occupations which should be further studied.